APLIKASI RANCANG BANGUN SISTEM INFORMASI AKUNTANSI PEMBELIAN SECARA TUNAI (STUDI KASUS: CV. PRESTASI GEMILANG JAKARTA) - Nining Suharyanti (Jurnal Akrab Juara, 2019)
In this globalization era, services and information that are fast and accurate and in accordance with needs have become a necessity, because of the many benefits that can be obtained from technology, for example, information produced with technology will be more accurate and faster, saving time and costs so that companies can increase revenue . To realize this, it requires a system that has been computerized, as a support for performance in terms of recording goods purchase transactions. Based on direct observations and the results of interviews the problems that occur are the systems used are still manual so that the recording process carried out has several weaknesses, such as the problem of loss of transaction data, a relatively long data search process, no integrated accounting records and timeliness in submitting accounting reports . Visual basic is one application that helps the system become computerized so that it becomes the best solution to solve these problems, so that in the data processing it is neatly organized, well integrated and in making financial reports more accurate.